2017
DOI: 10.1007/s10980-017-0501-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resilience of forested landscapes under climate change and management

Abstract: Context Resilience, the ability to recover from disturbance, has risen to the forefront of scientific policy, but is difficult to quantify, particularly in large, forested landscapes subject to disturbances, management, and climate change. Objectives Our objective was to determine which spatial drivers will control landscape resilience over the next century, given a range of plausible climate projections across north-central Minnesota. Methods Using a simulation modelling approach, we simulated wind disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…) contained 34 tree species (Table ) at a resolution of 4 ha (Lucash et al. ). The map was a compilation of plot data from the CNF and imputed U.S. Forest Service Forest Inventory and Analysis data (FIA; http://fia.fs.fed.us/) using three maps: two published studies (Wolter et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…) contained 34 tree species (Table ) at a resolution of 4 ha (Lucash et al. ). The map was a compilation of plot data from the CNF and imputed U.S. Forest Service Forest Inventory and Analysis data (FIA; http://fia.fs.fed.us/) using three maps: two published studies (Wolter et al.…”
Section: Methodsmentioning
confidence: 99%
“…, Lucash et al. ). This extension simulates aboveground and belowground growth of leaves, wood, fine roots, and coarse roots of each cohort on each site at a monthly timestep (Scheller et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…❖ www.esajournals.org 4 November 2019 ❖ Volume 10(11) ❖ Article e02934 forest succession and interactions with fire, harvest, wind, and insects (Scheller et al 2008, Duveneck et al 2014, Kretchun et al 2016, Krofcheck et al 2017, Lucash et al 2017. LANDIS-II uses the life-history traits of tree and shrub species, along with soil and climate data, to simulate succession and responses to disturbances over time.…”
Section: Overview Of Simulation Modelmentioning
confidence: 99%
“…In the Amazon rainforest, tree resilience to climate extremes is lower in floodplains than uplands, suggesting that vulnerability to wildfires is responsible for the pattern of spatial resilience (Flores et al, 2017). Forested landscape in north-central Minnesota showed that climate change would reduce resilience (Lucash, Scheller, Gustafson, & Sturtevant, 2017). Forested landscape in north-central Minnesota showed that climate change would reduce resilience (Lucash, Scheller, Gustafson, & Sturtevant, 2017).…”
mentioning
confidence: 99%